APLIKASI SISTEM INFORMASI LOKASI HOTEL BERBINTANG DI YOGYAKARTA BERBASIS WEBGIS - Arkiang, Wijayanto Prasetya; Sutanta, Edhy; Nurnawati, Erna Kumalasari (Jurnal Script, 2014)
ABSTRACTGeographic Information Systems (GIS) can facilitate the visitors, tourists, and business people and the general public to obtain information and the geographic location of the facility-star hotels in Yogyakarta are fast, accurate and complete. In addition, the location of the hotel is built GIS makes it easy for users to add locations, so that GIS-based web-site is always updated. Methodology conducted in several steps to build a software, software engineering, systems analysis, system design, system implementation, system testing and system maintenance. The software used, XAMPP, Photoshop, Dreamweaver, Notepad ++ and Google Maps as a server to display a map on a web page. The results show that the system can display the location of the hotel is in the Special Region of Yogyakarta (DIY) in accordance with the choice of hotel category, the system can also indicate the route to the destination location, addition of data in the system can be managed by admin.Keywords: GIS, hotel search and Google Map.